Anthropology for Architects. Social Relations and the Build Environment - Aguirre Núñez, Guillermo (Quaderns de l’Institut Català d’Antropologia, 2023)
Anthropology for Architects. Social Relations and the Built Environment. Ray Lucas (2020) London: Bloomsbury 264 p. ISBN: 978-1474241502